Digital financial inclusion: determinants of M-Shwari in Kenya - Kiptorus, Joan Jesang (Graduate School of Business (GSB), 2020)
Kenya has experienced unprecedented levels of growth in terms of mobile phone penetration and technological advancement, which is boosting financial sector development and subsequently spurring on economic growth. A report published by the Communications Authority of Kenya reported mobile phone penetration at 90.4%, with 41 million mobile phone subscribers as at December 2017. On the back of this, Kenya has made great strides in financial inclusion and with an overall score of 86%, received the top award for inclusive financial services from the Brookings Institution's 2017 Financial and Digital Inclusion Project. This was further reinforced by Financial Sector Deepening Kenya's findings that between 2006 and 2016, the number of fully excluded adults fell from 40% of the population to 17% of the population. One of the technological advancements that is helping bridge the financial inclusion gap is M-Shwari, a mobile banking product launched in Kenya in November 2012, through a collaborative effort between Safaricom and Commercial Bank of Africa. M-Shwari is available to M-Pesa customers and allows users to save and borrow from their mobile phones while earning interest on money saved. This study examined the determinants of M-Shwari usage for deposits and accessing loans. The study was conducted in the Kibera slum in Nairobi County in Kenya and used structured questionnaires to collect data over a six-month period (June 2017–December 2017). The target population was 250 000 persons, with an ultimate sample of 146 individuals. The study employed the Ordinary Least Squares regression technique to examine the drivers of financial inclusion, defined as the number of loans and deposits taken over the past six months on the M-Shwari platform, given respondents' gender, age, education, income, employment and number of dependants. Linear regressions were used to analyse the data. The logistic model was also employed to examine the likelihood of depositing with M-Shwari. The analysis reveals that women have a greater likelihood of using the M-Shwari service, which may indicate that mobile-based interventions could help bridge the gender gap in financial inclusion. While it was found that those who are employed have an increased likelihood of utilisation of the deposit M-Shwari feature, the assessment of determinants of M-Shwari deposits indicate that those who are employed are less likely to deposit money in M-Shwari. This may be due to the plethora of options at their disposal that offer superior benefits over and above those offered by M-Shwari. Education was also a significant determinant and the study found that those with higher levels of education were more likely to use the deposit feature of M-Shwari, but less likely to use the loan feature. The implication of this could be that those who were better educated were in a better position to weigh the pros and cons of loans from M-Shwari versus other sources. While an increase in income increased overall use of the M-Shwari service, a number of dependants linked to pressures on income meant that individuals with a higher number of dependants were less likely to deposit money with the M-Shwari service but more likely to borrow from the service to supplement their income.